The Analysis of Factors Related to the Company Performance with Capital Structure as an Intervening Variable in the Transportation Industry in Indonesia - Wiflihani Wiflihani; Elya Siska Anggraini; Raden Burhan Surya Nata Diningrat; Frisdo Ekardo (Budapest International Research and Critics University, 2021)
Theaterappeared in the 6th century BC from Ancient Greece as theatron which means drama. In those days, theaters were usually staged in a building called the Theatron. Theatron is a special building for drama performances, open without a roof, and built on terraces. The changing times and changing situations and conditions have made theater more developed. Developing in discourse and the birth of innovative theater works. Creative ideas from theatrical performances cannot be separated from the human side, politics, environment, religion, philosophy and other matters of morality. Starting from this the author tries to offer theater to be closer to the community. Revolution 4.0 is a point of awareness for a writer to see and observe the social phenomena of Indonesian society. With low literacy awareness in the form of reading, high productivity of society with the use of Gadged technology. Of course this is a serious problem that should be considered in the condition of the Indonesian people. This makes Tambak Bayan, Scientific Village of North Sumatra, become one of the objects of research. Tambak Bayan is a place to formulate directing concepts, ideas, and artistic values of the stage for the creation of a SITI theater performance as a form of community social reflection. Making theater a critical medium, involving the community as actors and actors/actresses who are directly involved in the creation of the theater. This will be strengthened by using Brect's theory. the concept that the entire performance apparatus, including the audience, is required to be at a distance. This concept is known by the wider community as verfremdungseffekt. Verfremdungseffekt itself can be interpreted as alienation, distance, or alienation. This concept is a very appropriate approach. Brect is a theater figure who brings a critical spirit to the theater and its audience.